Type D personality across general population and coronary patient samples in Iceland: Implications for cardiovascular health - Erla Svansdóttir 1979- (2012)
Doktorsritgerð varin við Háskólann í Tilburg, Hollandi The aim of this thesis was (1) to assess the validity of the Type D personality construct and its association with poor cardiovascular health in Icelandic patients with established CAD, and (2) to explore how Type D personality is related to cardiovascular health in the general Icelandic population. The studies presented in this thesis were funded by a grant from Rannís, the Icelandic Centre for Research.